Association between sleep and awake bruxism in patients with migraine - Godk, Keryn Sporh; Santos, Maria Luiza dos; Utiumi, Marco Antonio Takashi; Küster, João Guilherme Bochnia; Canalli Filho, Luiz Carlos; Kotsifas, Nikolai José Eustátios; Tan, Bin Cheng; Mioto, Eldislei; Colombani, Gabriel Eduardo Faria; Piovesan, Elcio Juliato (Headache Medicine, 2021)
Introduction When migraine undergoes transformation from episodic to chronic form it becomes more disabling due to the refractoriness in treatment and the emergence of comorbidities, with the establishment of a bidirectional relationship between sleep bruxism and chronic migraine. This study aimed to assess whether sleep and awake bruxism are more prevalent in chronic migraine when compared to episodic migraine and also to establish possible clinical correlations with the process of chronification. Methods 210 patients were allocated to the study, 97 with episodic migraine and 113 with chronic migraine, who underwent face-to-face interviews with the completion of the scales: specific questionnaire for the diagnosis of sleep and awake bruxism, PHQ-9 (depression), GAD-7 (anxiety), Epworth Scale (daytime sleepiness), MIDAS (migraine incapacity) and HIT-6 (impact of headache). Results The prevalence of sleep and awake bruxism was similar in patients with episodic versus chronic migraine (p = 0.300 and p = 0.238). The correlation of patients with concomitant awake and sleep bruxism and with high scores on the migraine incapacity (MIDAS) and headache impact (HIT-6) scales was higher among patients with chronic migraine than in patients with episodic migraine. (p <0.001 and p <0.001). Conclusion Sleep and awake bruxism alone are not more prevalent in chronic migraine when compared to episodic migraine, although bruxism causes greater impact and disability on individuals with chronic migraine.